Advancements in Nanoemulsion-Based Drug Delivery Across Different Administration Routes - Maria D. Chatzidaki; Evgenia Mitsou (Pharmaceutics)
Nanoemulsions (NEs) have emerged as effective drug delivery systems over the past few decades due to their multifaceted nature, offering advantages such as enhanced bioavailability, protection of encapsulated compounds, and low toxicity. In the present review, we focus on advancements in drug delivery over the last five years across (trans)dermal, oral, ocular, nasal, and intra-articular administration routes using NEs. Rational selection of components, surface functionalization, incorporation of permeation enhancers, and functionalization with targeting moieties are explored for each route discussed. Additionally, apart from NEs, we explore NE-based drug delivery systems (e.g., NE-based gels) while highlighting emerging approaches such as vaccination and theranostic applications. The growing interest in NEs for drug delivery purposes is reflected in clinical trials, which are also discussed. By summarizing the latest advances, exploring new strategies, and identifying critical challenges, this review focuses on developments for efficient NE-based therapeutic approaches.